2022
DOI: 10.1017/s0305000922000149
|View full text |Cite
|
Sign up to set email alerts
|

Can gesture input support toddlers’ fast mapping?

Abstract: Forty-eight toddlers participated in a word-learning task to assess gesture input on mapping nonce words to unfamiliar objects. Receptive fast mapping and expressive naming for target object-word pairs were tested in three conditions – with a point, with a shape gesture, and in a no-gesture, word-only condition. No statistically significant effect of gesture for receptive fast-mapping was found but age was a factor. Two year olds outperformed one year olds for both measures. Only one girl in the one-year-old g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…An additional limitation of the study was data collection using only a referent identification task. Although pilot testing indicated that children struggled to produce novel words on demand, consistent with Foran et al (2023), inclusion of a novel word production task in addition to a referent identification task would yield additional data providing insights into the effects of beat gesture and contrastive accenting on novel word learning in early childhood. Finally, the word learning task used in the current study had limited discursive context, and novel word knowledge was only tested immediately following learning.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…An additional limitation of the study was data collection using only a referent identification task. Although pilot testing indicated that children struggled to produce novel words on demand, consistent with Foran et al (2023), inclusion of a novel word production task in addition to a referent identification task would yield additional data providing insights into the effects of beat gesture and contrastive accenting on novel word learning in early childhood. Finally, the word learning task used in the current study had limited discursive context, and novel word knowledge was only tested immediately following learning.…”
Section: Discussionmentioning
confidence: 73%
“…The findings of the current study add to the literature on the comprehension of emphasis cues in early childhood by demonstrating that interpretation of beat gesture in a contrastive word learning task varies with age by sex. Previous work suggests that girls’ language development in early childhood outpaces that of boys in several respects (Lange et al, 2016), and that infant and toddler girls produce more types of referential gestures and gesture-word combinations than boys (Eriksson et al, 2012; Germain et al, 2022; Özçalışkan & Goldin-Meadow, 2010) and are more likely to name objects learned with referential gestures than boys (Foran et al, 2022). With respect to non-referential beat gesture development, the results of previous studies fail to provide evidence of sex differences (Austin & Sweller, 2014; Colletta et al, 2010; Igualada et al, 2017; Mathew et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations